Direct foaming of Al2O3-based macroporous ceramics containing pre-foamed colloidal alumina, calcite and CAC suspension. Issue 16 (15th August 2021) - Finhana, I.C.; Borges, O.H.; Santos, T.; Salvini, V.R.; Pandolfelli, V.C.
Abstract: Adding pre-foamed colloidal alumina to ultrastable Al2 O3 -stabilised foams can be a path towards partially counteracting the firing shrinkage of these materials and producing macroporous ceramics with smaller pores. Nevertheless, this system still presents a long setting time and high sintering-induced shrinkage, which hinders the production of larger samples and reduces its porosity. In the present work, it was observed that adding calcium aluminate cement suspension (CACS ) and CaCO3 (calcite) to the aforementioned system can speed up its solidification kinetics, improve its mechanical strength and reduce its shrinkage after firing, maintaining high porosity and smaller pore sizes. By using these raw materials, samples with an average pore size below 60 μm, total porosity above 70%, and a narrower pore size distribution were attained after thermal treatment at 1600 °C for 5h. Moreover, due to the in situ formation of calcium hexaluminate, their shrinkage after sintering was almost halved (from 20% to 11%).